2008
DOI: 10.1097/jsm.0b013e31815cdd37
|View full text |Cite
|
Sign up to set email alerts
|

Athletic Performance and Serial Weight Changes During 12- and 24-Hour Ultra-Marathons

Abstract: Our findings demonstrate that the majority of weight decrease/dehydration in both the 12- and 24-hour races occurred during the first 8 hours. Hence, to maintain body weight, fluid intake should be optimized in the first 8 hours for both 12- and 24-hour runners and in 16 to 20 hours for 24-hour marathon runners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
73
3
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(88 citation statements)
references
References 13 publications
10
73
3
1
Order By: Relevance
“…This finding supports those of Clark et al [4]; who reported that dehydration at the end of day two was positively associated with performance and Kao et al [12]; who showed a significant relationship between percentage BM loss in a 24 hour ultra-marathon and performance. These findings contradict those of McConell et al [10] and Fallowfield et al [11], who previously reported negative effects of dehydration on endurance exercise performance in temperate climes.…”
Section: Hydration Status With Performancesupporting
confidence: 90%
See 2 more Smart Citations
“…This finding supports those of Clark et al [4]; who reported that dehydration at the end of day two was positively associated with performance and Kao et al [12]; who showed a significant relationship between percentage BM loss in a 24 hour ultra-marathon and performance. These findings contradict those of McConell et al [10] and Fallowfield et al [11], who previously reported negative effects of dehydration on endurance exercise performance in temperate climes.…”
Section: Hydration Status With Performancesupporting
confidence: 90%
“…A meta-analysis of two research articles and eight individual studies reported drinking according to the dictate of thirst was associated with an increase in TT performance compared with a rate of drinking below (+5.2 ± 4.6%, p = 0.01), or above (+2.4 ± 5.0%, p = 0.40), thirst [39]. This could account for why dehydration has not been found to negatively affect performance in many observational studies on "real-life" events when participants are free to drink as they desire [4,12], providing fluids are available.…”
Section: Hydration Status With Performancementioning
confidence: 92%
See 1 more Smart Citation
“…During ultra-marathon running, the largest decreases in body mass occur in the first hours of the race [55]. Large fluid intakes might, however, lead to an increased risk for exercise-associated hyponatremia, defined as plasma sodium concentration [Na + ] <135 mmol/l.…”
Section: Fluid and Electrolyte Metabolism During Ultra-runningmentioning
confidence: 99%
“…A decrease in body mass is considered to be the result of dehydration in marathoners [1,2] and ultra-marathoners [3]. In a marathon with an average duration of about 3 h, body mass decreased by 2 kg [2]; in an ultra-marathon such as a 24-h run, body mass decreased by 2 kg [4] up to 2.5 kg [3].…”
Section: Introductionmentioning
confidence: 99%